Fifteenth General Review of Quotas : Report of the Executive Board to the Board of Governors. (Policy Papers; Policy Paper, 2016)
In completing the Fourteenth General Review of Quotas (hereafter the 'Fourteenth Review') and approving the proposed Amendment on the Reform of the Executive Board (hereafter the 'Board Reform Amendment'), the Board of Governors requested the Executive Board to bring forward the timetable for completion of the Fifteenth General Review of Quotas (hereafter the 'Fifteenth Review') to January 2014.